2021
DOI: 10.3201/eid2710.211298
|View full text |Cite
|
Sign up to set email alerts
|

Seoul Virus Associated with Pet Rats, Scotland, UK, 2019

Abstract: We describe a case of hemorrhagic fever with renal syndrome caused by Seoul virus in a woman in Scotland, UK. Whole-genome sequencing showed the virus belonged to a lineage characterized by recent international expansion, probably driven by trade in pet rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The infection is correlated to human-rodent interactions, and so in developed countries, some professional people are more exposed to the risk of contracting the disease (forest workers, pet rats owner, laboratory personnel trapping workers, hunters) [84][85][86][87], meanwhile, in rural or developing countries, the risk is also widespread among the general population [88,89]. Several serological studies have been conducted in many countries of the world, revealing the variable prevalence of it from 6% to 36% [90][91][92][93][94][95].…”
Section: Hantavirusesmentioning
confidence: 99%
“…The infection is correlated to human-rodent interactions, and so in developed countries, some professional people are more exposed to the risk of contracting the disease (forest workers, pet rats owner, laboratory personnel trapping workers, hunters) [84][85][86][87], meanwhile, in rural or developing countries, the risk is also widespread among the general population [88,89]. Several serological studies have been conducted in many countries of the world, revealing the variable prevalence of it from 6% to 36% [90][91][92][93][94][95].…”
Section: Hantavirusesmentioning
confidence: 99%
“…In Europe, several studies evaluated the occurrence of SEOV in pet, breeder, and wild rats and detected human disease cases caused by SEOV transmission by pet rats [ 13 , 14 ]. SEOV, which was detected in pet and breeder rats from Great Britain [ 15 ] and the Netherlands [ 16 ] as well as in a pet rat in Sweden that had been imported from England [ 17 ], was associated with human disease cases [ 13 , 14 ]. Studies on wild rats from Belgium indicated the presence of SEOV-reactive antibodies [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Vertical transmission is less likely because rodent progeny are protected by maternal antibodies ( 5 ). Since 2013, human hantavirus infections transmitted by pet rats have been reported in countries in Europe and the United States ( 6 , 7 ). In the Netherlands, quantitative reverse transcription PCR (RT-PCR) testing revealed 12.2% positivity among feeder rats not linked to human SEOV cases ( 8 ).…”
mentioning
confidence: 99%